Battle Harbour in Transition: Merchants, Fishennen, and the State in the Struggle for Relief in a Labrador Community during the 1930s - Cadigan, Sean (Labour/Le Travailleur, 1990)
Abstract The early 1930s witnessed the deterioration of truck relationships between fishermen and merchants in Battle Harbour, a Newfoundland fishing community located on the coast of Labrador. By taking advantage of changes in the fishery, more prosperous fishermen began to deal with other firms, undercutting Baine, Johnston's domination of Battle Harbour. As Baine, Johnston withdrew winter credit, poorer fishermen threatened the firm with direct, violent action which neither the merchant nor the state were able to deal with except by granting relief. Such actions by Battle Harbour fishermen indicate that they were able to step outside the supposed limits of the culture of their kin-based villages, and confront directly the exploitation of merchant capital in the cod fishery.